Neutrophil‐to‐lymphocyte ratio and risk of lung cancer mortality in a low‐risk population: A cohort study. Issue 12 (14th September 2019) - Kang, Jihoon; Chang, Yoosoo; Ahn, Jiin; Oh, Sukjoong; Koo, Dong‐Hoe; Lee, Yun‐Gyoo; Shin, Hocheol; Ryu, Seungho
Abstract : Neutrophil‐to‐lymphocyte ratio (NLR) is associated with poor prognosis in patients with lung cancer, but the predictive role of NLR on the risk of developing lung cancer is unknown. We investigated the association between NLR and lung cancer mortality in lung cancer‐free adults. A cohort study was performed with 527, 124 Korean adults who were free of lung cancer and were followed for up to 16 years. Vital status and lung cancer‐related deaths were ascertained through national death records. Hazard ratios (HRs) and 95% confidence intervals (CIs) for lung cancer mortality were estimated using a Cox proportional hazards model. During 4, 567, 495.8 person‐years of follow‐up, 574 lung cancer deaths were identified. A higher NLR was positively associated with lung cancer mortality. The multivariable‐adjusted HR (95% CI) for lung cancer mortality comparing quintiles 2, 3, 4 and 5 of NLR to the lowest quintile were 1.26 (0.96–1.67), 1.23 (0.93–1.63), 1.33 (1.01–1.75) and 1.47 (1.13–1.92), respectively. The highest risk of lung cancer mortality was also observed in the highest NLR quintile among never‐smokers and low‐risk individuals after adjusting for lung function and other possible confounders. Platelet‐to‐lymphocyte ratio showed an inverse J‐shaped association with lung cancer mortality in men but the trends in women, low‐risk individuals or never‐smokers were neither linear nor U‐shaped. In this large cohort of young and middle‐aged individuals, NLR was independently associated with increased risk of lung cancer mortality in low‐risk individuals, indicating a role of systemic inflammation in lung cancer mortality in our study population. Abstract : What's new? Neutrophil‐to‐lymphocyte ratio (NLR) is associated with poor prognosis in patients with lung cancer, but the predictive role of NLR on the risk of developing lung cancer is unknown. Here, the authors investigated the association between NLR and lung cancer mortality in a large prospective cohort study of 527, 124 cancer‐free adults. The study reveals the association of elevated NLR with increased risk of lung cancer mortality, which was consistently observed in both never‐smokers and low‐risk individuals. NLR, a systemic inflammation marker, may thus play a role as an independent predictor of lung cancer mortality in never‐smokers as well as low‐risk populations.